Living as the people of God : the relevance of Old Testament ethics - Wright, Christopher J. H. (Inter-Varsity Press, 1983)
Takes Old Testament laws in their context and examines their major themes, covering economics, politics, crime and punishment, due process of law and more. Written in a lively, readable style.